Unveiling the leadership essence: exploring the authenticity of primary school headmasters in Malaysia - Mat Zaid, Mohammad Zainuddin; Yusof, Mat Rahimi; Awang, Mohd Ish (Institute of Advanced Engineering and Science, 2024)
The development of the current modernity in regardless of the explosion of industrial revolution 4.0 (IR4.0) in the 21st millennium has influenced the leaders of educational institutions towards the transformations of the effective organizational leadership. Therefore, this study is aimed to identify and redetermine the factors that influence the authentic leadership practices among the headmasters. The quantitative study using the cross-sectional research from the adaptation of authentic leadership questionnaire (ALQ) based instruments has been distributed to 436 teachers via online, as they were also being randomly selected through a stratified simple random sampling technique. The study data has been analyzed through the descriptive statistics and exploratory factor analysis (EFA), as a confirmatory procedure and an analysis factor (CFA) using IBM-SPSS-AMOS software. The results of the study shows that all four dimensions of authentic leadership are at a high-level course. Meanwhile, the CFA analysis showed that the four dimensions together with the 16 indicator items in authentic leadership, were accepted and confirmed. In addition, the data analysis also found out that the influence of all dimensions in the authentic leadership of headmasters are in positive and at a high rate. Finally, this study has successfully developed a measurement model for the authentic leadership of headmasters. In spite of that, it is suggested that a further studies on a larger scale which involves the qualitative and quantitative methods could be carried out by the future researchers in providing greater benefits and better contributions in the next findings